2006
DOI: 10.1111/j.1440-1681.2006.04440.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Pravastatin in Murine Lipopolysaccharide‐induced Acute Lung Injury

Abstract: 1. The present study was designed to determine whether pravastatin, a 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, could attenuate acute lung injury (ALI) induced by lipopolysaccharide (LPS) in BALB/c mice. 2. Acute lung injury was induced successfully by intratracheal administraiton of LPS (3 microg/g) in BALB/c mice. Pravastatin (3, 10 and 30 mg/kg, i.p.) was administered to mice 24 h prior to and then again concomitant with LPS exposure. 3. Challenge with LPS alone produced a significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 25 publications
(41 reference statements)
2
48
0
3
Order By: Relevance
“…at ASPET Journals on May 10, 2018 jpet.aspetjournals.org tin, suggesting that the inhibition of ALI by pitavastatin may be associated with its decreasing effect on TNF-␣ (Yao et al, 2006). Likewise, the ability of pitavastatin to mitigate the increases in circulating levels of TNF-␣ and IL-6 after CLPinduced sepsis was demonstrated in this study.…”
Section: Statin and Alveolar Macrophage In Sepsis 387mentioning
confidence: 54%
See 1 more Smart Citation
“…at ASPET Journals on May 10, 2018 jpet.aspetjournals.org tin, suggesting that the inhibition of ALI by pitavastatin may be associated with its decreasing effect on TNF-␣ (Yao et al, 2006). Likewise, the ability of pitavastatin to mitigate the increases in circulating levels of TNF-␣ and IL-6 after CLPinduced sepsis was demonstrated in this study.…”
Section: Statin and Alveolar Macrophage In Sepsis 387mentioning
confidence: 54%
“…The data are in good agreement with those obtained with other statins in LPS-challenged mice. Thus, simvastatin and pravastatin have been shown to significantly decrease intratracheal LPS-induced murine lung vascular leak and inflammation (Jacobson et al, 2005;Yao et al, 2006). Taken together, these results would implicate the potential for the class of drugs known as statins to serve as a novel therapeutic tool in ALI.…”
Section: Discussionmentioning
confidence: 69%
“…This is the first study to find this effect in the pulmonary compartment in humans, although previous animal studies have demonstrated that statins attenuate TNF-a release in BALF after intratracheal administration of LPS in mice (44). TNF-a is characteristically induced in, and secreted by, LPSstimulated alveolar macrophages (33,35) and is NF-kB-dependent (45).…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, the potential for therapies that reduce cellular and serum cholesterol to reduce PMN recruitment to the airspace has also been reported. Three different hydroxy-methylglutaryl coenzyme A reductase inhibitors (''statins'') used to treat clinical hypercholesterolemia have now been shown to reduce PMN recruitment to and microvas-cular injury within the rodent lung following LPS exposure (80)(81)(82), likely due to dual effects upon PMN chemotaxis and endothelium. Statins also enhance clearance of apoptotic PMNs by alveolar macrophages (83).…”
Section: Emerging Roles For Cholesterol In Pmn Recruitment To the Lungmentioning
confidence: 99%